Effectiveness of Music-Based Intervention in Improving Uncomfortable Symptoms in ICU Patients: An Umbrella Review - Yu-Fen Chen (MDPI AG, 2021)
Background: Intensive care unit (ICU) patients experience multiple uncomfortable symptoms, which may be alleviated using music-based intervention, a nondrug treatment. This umbrella review aims to combine the data of systematic reviews and/or meta-analyses to evaluate the effectiveness of music-based intervention in improving uncomfortable symptoms in ICU patients. Methods: A comprehensive literature search was performed on the PubMed, Embase, Cochrane Library, Airiti Library, CINAHL, ProQuest, and Web of Science databases, and Epistemonikos. The search had no language restrictions, and articles on the improvement of symptoms using music-based intervention in adult ICU patients were included. This review protocol was registered on PROSPERO (CRD42021240327). Results: This umbrella review retrieved 5 systematic reviews and 41 original studies, including 39 randomized controlled trials, and 2 nonrandomized controlled trials. Diverse music was the most common music type used for music-based intervention, the intervention music was typically decided by the study participants (61%), and most subjects underwent one intervention session (78%). Furthermore, most music intervention sessions lasted for 30 min (44%). The positive results included decreased anxiety, decreased pain, decreased agitation, decreased anesthesia dose and sedative use, decreased chances of delirium, decreased feelings of uncomfort, and improved sleep quality. Conclusions: A systematic review on the effectiveness of music-based intervention in improving uncomfortable symptoms in ICU patients revealed that 20–30 min intervention sessions showed the best improvement in the uncomfortable symptoms in patients. This study provides a basis for using music-based intervention to relieve the uncomfortable symptoms in critically ill ICU patients, and a reference for empirical clinical practice.